Simulating Adaptive Quests for Increased Player Impact in MMORPGs - Tomai, Emmett; Salazar, Rosendo (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2012)
In this paper, we present adaptive quests, an extension to the dominant quest model that guides and motivates gameplay in MMORPG shared worlds. The standard model has proven effective, but is significantly incompatible with the desire for player driven change in the world. We present an incremental step to increasing player impact, discuss the problems it creates with the quest model, and show how adaptive quests can help reconcile the two. We present simulation experiments supporting not only that adaptive quests help mitigate those problems, but that they can actually improve them over the standard model.